Teología platónica: a propósito de la Idea Suprema de Bien en la República - Acosta, Jean Seas (2019)
The supreme idea of the good constitutes an investigative problem that deserves reflection because it is possible to determine in Plato, the first theologian of the west. The theology told by the Athenian is tinged by the ontological dimension of reality, where the existence of God can be understood as the foundation of all reality; therefore, it is only possible to have moral consequences to a posteriori. This conception implies that it's proper contemplation should be carried out through relegation instead of religion. Keywords: Plato, Republic, Good, Zubiri, relegation